2012
DOI: 10.1089/ast.2011.0729
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Generations of Carbon in the Apex Chert and Implications for Preservation of Microfossils

Abstract: While the Apex chert is one of the most well-studied Archean deposits on Earth, its formation history is still not fully understood. Here, we present Raman spectroscopic data collected on the carbonaceous material (CM) present within the matrix of the Apex chert. These data, collected within a paragenetic framework, reveal two different phases of CM deposited within separate phases of quartz matrix. These multiple generations of CM illustrate the difficulty of searching for signs of life in these rocks and, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 38 publications
4
69
1
Order By: Relevance
“…Our nonbiological formation model, consistent with multiple fluid flow events (30,31), is: (i) hydration of mica flakes (abundant in the country rock) during widespread hydrothermal activity resulting in vermiculite-like phyllosilicate formation; (ii) continued heating plus rapid expulsion of water from phyllosilicate crystal lattices, causing exfoliation (i.e., accordion-like expansion at right angles to the cleavage plane), and creating the initial vermiform morphological expression of microfossil-like artifacts; and (iii) adsorption of later hydrocarbons (and locally additional iron) onto the vermiculite, mimicking cell walls. We note that exfoliated vermiculite has high adsorption capacity resulting from the strong capillary action of slit-like pores between plate-like grains (27), encouraging its use for cleaning up oil spills (27,32).…”
Section: The Gunflint Chert: New Analytical Techniquessupporting
confidence: 77%
See 2 more Smart Citations
“…Our nonbiological formation model, consistent with multiple fluid flow events (30,31), is: (i) hydration of mica flakes (abundant in the country rock) during widespread hydrothermal activity resulting in vermiculite-like phyllosilicate formation; (ii) continued heating plus rapid expulsion of water from phyllosilicate crystal lattices, causing exfoliation (i.e., accordion-like expansion at right angles to the cleavage plane), and creating the initial vermiform morphological expression of microfossil-like artifacts; and (iii) adsorption of later hydrocarbons (and locally additional iron) onto the vermiculite, mimicking cell walls. We note that exfoliated vermiculite has high adsorption capacity resulting from the strong capillary action of slit-like pores between plate-like grains (27), encouraging its use for cleaning up oil spills (27,32).…”
Section: The Gunflint Chert: New Analytical Techniquessupporting
confidence: 77%
“…More importantly, a biogenic carbon source can create microfossil-like artifacts when redistributed from either adjacent units or from biological communities within the system. Recent studies have shown that there are multiple populations of carbonaceous material within the Apex chert (29)(30)(31), each with different thermal alteration histories, suggesting repeated episodes of carbon introduction and/or redistribution within this unit. This has been interpreted to result from multiple pulses of hydrothermal and metamorphic activity, fluid flow, and weathering (30,31), providing ideal conditions for the creation of carbonaceous microfossil-like artifacts.…”
Section: The Gunflint Chert: New Analytical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…3.5 Ga Apex chert hydrothermal vein (refer to Olcott Marshall et al, 2012a for locality and thin section details) and research-grade hematite 49-5908 purchased from Wards Natural Science.…”
Section: Resultsmentioning
confidence: 99%
“…By the end of 1978, the 50 th anniversary of Raman's discovery, 24,000 papers dealing with various kinds of Raman effect had been published. Raman spectroscopy is becoming increasingly popular in geoscience applications, as astrobiologists, geologists, paleontologists, and planetary and space scientists discover the wealth of nondestructive mineral and organic molecule/macromolecule data that Raman spectroscopy can afford (e.g., Bény, 1992, 1999;Wopenka and Pasteris, 1993;Beyssac et al, 2002;Wang et al, 2004Wang et al, , 2006Marshall et al, 2010Olcott Marshall et al, 2012aEdwards et al, 2013).…”
Section: Introductionmentioning
confidence: 99%